2019
DOI: 10.1002/adom.201801683
|View full text |Cite
|
Sign up to set email alerts
|

Light Control with Liquid Crystalline Elastomers

Abstract: The facile synthesis of well-aligned, main-chain liquid crystalline elastomers (LCEs) that retain the cholesteric phase (CLCEs) is reported. The selective reflection inherent to this phase is thermally tuned more than 200 nm in these solid films, across the visible spectrum. The optical response is directly correlated to thermomechanical expansion of the CLCE film thickness. The bandwidth of the selective reflection of the CLCEs is increased to more than 200 nm by the incorporation of photosensitive chiral dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 50 publications
2
96
0
Order By: Relevance
“…More recent approaches utilized electric/magnetic fields or surface alignment from sacrificial or integrated substrates, but scalability and robustness are still critical issues. The procedures involve, for example, mixing of reactive monomers at high temperature, breaking open sandwich cells and peeling off CLCE films from the substrates without rupture, soaking in solvents to remove unreacted materials, and sometimes custom synthesized chemicals are required . To fully exploit the technological potential of CLCEs, a significantly simplified and robust procedure to make unsupported highly elastic CLCEs is needed, allowing a fast and reversible color shift across the full visible spectrum in response to strain.…”
Section: Introductionmentioning
confidence: 99%
“…More recent approaches utilized electric/magnetic fields or surface alignment from sacrificial or integrated substrates, but scalability and robustness are still critical issues. The procedures involve, for example, mixing of reactive monomers at high temperature, breaking open sandwich cells and peeling off CLCE films from the substrates without rupture, soaking in solvents to remove unreacted materials, and sometimes custom synthesized chemicals are required . To fully exploit the technological potential of CLCEs, a significantly simplified and robust procedure to make unsupported highly elastic CLCEs is needed, allowing a fast and reversible color shift across the full visible spectrum in response to strain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous freely‐standing CLCE films have demonstrated control over color changes through thermal and mechanical strain, yet lack the ability to permanently reconfigure the optical characteristics as demonstrated here. [ 13,18,19 ] We demonstrate both reversible color and shape change through transient application of strain and also permanent reconfiguration of color and shape through photoactivated AFT‐based DCC. [ 20 ] To achieve these outcomes, films were prepared with all the necessary elements; crosslinking, an LCE host, a chiral LC monomer, a radical photoinitiator, and incorporation of AFT‐capable moieties throughout the network.…”
Section: Resultsmentioning
confidence: 99%
“…designed a crosslinked freely‐standing cholesteric liquid crystal elastomer (CLCE) film that changes color via heating, which slightly increases the thickness of the sample and thus the pitch spacing, changing the wavelength of light that the polymer reflects. [ 18 ] For a more dramatic demonstration of strain changes linked to color change, Finkelmann et al. designed a PDMS dye doped CLCE that alters the wavelength transmitted through mechanical strain.…”
Section: Introductionmentioning
confidence: 99%
“…Photonic coatings of temperature-responsive non-polymerized Ch-LC mixtures encapsulated in polymer protective layers were recently reported, showing a good stability and bandshift range by the Sm-Ch pre-transitional effect, but a subtle stratification process is required for their fabrication [17][18][19]. Alternative ways to make temperature-responsive photonic polymer coatings use either the humidity [20] or heat expansion of the materials [21,22], which are not able to induce a large reflection band shift without the presence of water. Soft polymers such as polysiloxane Ch-LC elastomers or semi-interpenetrating polymer networks based on oligosiloxanes or a Ch-LC polymer network have been reported that showed temperature-responsive optical changes [23,24], but the shift of the reflection band was limited.…”
Section: Introductionmentioning
confidence: 99%